Answers of a Rumanian village to the economic and social challenges - György Katalin Takács; Izolda Szabó Ábrahám; Izabella Bakos; István Takács (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 3rd Edition of the International Symposium, October 2012, Bucharest, 2012)
Economic and social changes that took place in Eastern Europe in the 1990's, created a particularly difficult situation for the rural population, especially for those who pursue agricultural production. Those developmental differences that previously characterized the regions, settlements are not moderated significantly after the EU accession of Romania either. However, after the accession numerous positive changes have happened, that help the livability of rural areas. The developed land structure, the production structure of agriculture does not serve the economy effectively, it cannot or it can produce real commodities at a limited extent. An economic survey had been conducted at Mezîomadaras in 2002 and with the partial repetition of the development proposal based on the survey in the summer of 2012 the research looking for answers to the questions, to what extent and in which direction the changed the economy of the village examined, what elements of the development concept achieved. The article shows that how the development, creation of the settlement's infrastructure background (road network), the agricultural, sales information, contribute to some farmers' development to commodity producer, and point out that the cooperation is not typical, the tender activity is very low, despite that the rate of livestock farmers is high.
Keywords: 330; rural development; interview